MEDEX 2015: Heart rate variability predicts development of acute mountain sickness - Sutherland, A.; Freer, J.; Evans, L.; Dolci, A.; Crotti, M.; Macdonald, J. H. (High Altitude Medicine & Biology, 2017)
Aims: Acute mountain sickness (AMS) develops when the body fails to acclimatize to atmospheric changes at altitude. Preascent prediction of susceptibility to AMS would be a useful tool to prevent subsequent harm. Changes to peripheral oxygen saturation (SpO2) on hypoxic exposure have previously been shown to be of poor predictive value. Heart rate variability (HRV) has shown promise in the early prediction of AMS, but its use pre-expedition has not previously been investigated. We aimed to determine whether pre- and intraexpedition HRV assessment could predict susceptibility to AMS at high altitude with better diagnostic accuracy than SpO2.